Classification of critical aging segments of power transmission lines - Mohamed Ariffin, Nur Azliatun Hisan (2011)
An Analytic Hierarchy Process (AHP) approach been used for analysis, comparison and classify the quality of several parameters that affect the conductor thermal ratings. The method is based on pairwise comparison between several factors that affect the alternatives in a hierarchical structure. The thermal ratings of power transmission lines is basically based on the maximum permissible temperature of the conductors. Conductor can lose their tensile strength due to thermal load or annealing. This paper analysis thermal aging using known characteristics of transmission conductor, load information and weather data. By analyzing the conductor temperatures, aging due to loss of conductor tensile strength is estimated at individual locations along the transmission corridor. The proposed methodology is illustrated using a case study analyzing a power transmission line in Kluang, Johor. This information is important for transmission network operating procedures, scheduling of line inspections, maintenance, or reconductoring.